Pattern recognition applications and methods : 6th International Conference, ICPRAM 2017, Porto, Portugal, February 24-26, 2017, Revised selected papers /: 6th International Conference, ICPRAM 2017, Porto, Portugal, February 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available